Perception of UiTMCS staff towards the implementation of five days working week / Rody Bunsu … [et. al] - Bunsu, Rody; Abdul Razak, Rozaida; Mat Darus, Rusmalikhairol; Abdul Rahman, Saifuddin Omar; Syed Mad Damhuri, Syarifah Suraya (2006)
Five days working work has been successfully implemented in government sectors since July 1, 2005 and the declaration has been made by Prime Minister of Malaysia, Datuk Seri Abdullah Ahmad Badawi. The study examines the UiTMCS staffs perception and impact regarding the government’s policy five days working week. Random samples of 150 academic and non - academic staffs in UiTMCS were interviewed regarding the implementation. On the staffside, their working hour and more free time has been increased at the same time. Most ofthe staffs are highly welcomed the implementation since it gives those benefits rather than drawbacks.